Behavior of H2O surrounding NH4+ and Al3+ in NH4Al(SO4)2·12H2O by 1H MAS NMR, 14N NMR, and 27Al NMR. Issue 87 (5th December 2017) - Lim, Ae Ran
Abstract : In order to understand the thermodynamic properties and structural geometry of NH4 Al(SO4 )2 ·12H2 O, we studied the magic angle spinning nuclear magnetic resonance (MAS NMR) and static NMR as a function of temperature. Abstract : In order to understand the thermodynamic properties and structural geometry of NH4 Al(SO4 )2 ·12H2 O, we studied the magic angle spinning nuclear magnetic resonance (MAS NMR) and static NMR as a function of temperature. The changes of the chemical shifts, linewidths, resonance frequencies, and spin–lattice relaxation times for 1 H, 14 N, and 27 Al nuclei near T d (=335 K), which is interpreted as the onset of partial thermal decomposition, are due to the structural phase transition. The changes near T d are related to the loss of H2 O, which probably disrupts the forms of the octahedra of water molecules surrounding NH4 + and Al 3+ ions. This mechanism above T d is related to hydrogen-bond transfer involving the breakage of the weak part of the hydrogen bond.